The Effect of the PhET Assisted Problem Based Learning Model on Student Learning Outcomes in Wave Material - Esa Imaniah; Susilawati Susilawati; Sutrio Sutrio; Kosim Kosim (Postgraduate, University of Mataram, 2023)
This study aims to examine whether or not there is an influence of the PhET-assisted problem-based learning model on student learning outcomes in Wave material. The type of research used is a quasi-experimental research design with Nonquivalent Control Group Design. The population in this study were all students in class XI MAN 1 Mataram with the sample being students in class XI MIPA 3 with a total of 31 students as the control class and students in class XI MIPA 4 with a total of 29 students as the experimental class. The test instrument used is in the form of multiple choice questions. Before the test instrument is given, the instrument is tested first, namely testing validity, reliability, difficulty level, and discriminating power. The results of the analysis showed that the average score of the physics learning outcomes of students who were taught with the PhET-assisted problem-based learning model was 79.65 and students who were taught without using PhET had an average value of 69.77. The results of testing the hypothesis using the t-test obtained a t-count of 6.45 and a t-table of 2.0017. Thus the value of t-count is greater than t-table then Ha is accepted and H0 is rejected. This means that there is an influence of the PhET-assisted problem-based learning model on student learning outcomes in class XI MAN 1 Mataram class wave material.